Contribuições para a construção de políticas públicas de orientação profissional no Brasil a partir de programas modelo - Suzuki, Egypcialinda Camargo (2016)
This study aimed to identify models that can contribute to public policy professional guidance can be designed, taking into account laws in force and bills under consideration. We searched the legislation guidelines that promote or regulate the professional guidance, we sought to further identify Act projects aimed at the implementation of vocational guidance programs in Brazil. This study was divided into two stages. The first of desk research, which were analyzed and Laws Project Federal Laws that deal with the implementation of vocational guidance for students. The second literature, they were found in the literature articles that present vocational guidance programs that can be used as a model and that can contribute to the development of public policies of vocational guidance. This research identified that the Brazilian legislation does not favor the vocational guidance as practice for public school students. In the absence of public policies of vocational guidance this work aimed to analyze 8 Career Guidance Program models that enable the articulation of Public Professional Oirentação Policies.